Gambaran Karakteristik Korban dan Pola Luka Luar Korban Mati Pengendara Sepeda Motor Akibat Kecelakaan Lalu Lintas di RS Bhayangkara TK II Sartika Asih Bandung Tahun 2020-2024 - Ananda Alamsiah; Andri Rusman; Lina Damayanti (Health & Medical Sciences, 2026)
Traffic accidents are a leading cause of death worldwide, with motorcycle-related fatalities increasing annually. This study aimed to describe the characteristics of victims and patterns of external injuries in deceased motorcyclists due to traffic accidents at Bhayangkara TK II Sartika Asih Hospital, Bandung, from 2020 to 2024. A retrospective descriptive study was conducted using medical records and Visum et Repertum of 56 victims. Results showed that most victims were aged 18–29 years  (39.3%) and male  (80.4%). The most common injury locations were the head and lower extremities  (71.4%), with abrasion being the predominant injury pattern  (96.4%). All cases underwent external examination  (100%). Young adults aged 18–29 years dominated the cases, reflecting their high mobility and risk-taking behavior. Male victims were most common, likely due to driving habits. Abrasions occurred frequently, caused by friction with road surfaces during falls. The head and lower extremities were the most vulnerable regions, highlighting the need for enhanced safety measures)